Leclercia adecarboxylata Musculoskeletal Infection in an Immune Competent Pediatric Patient: An Emerging Pathogen? - W. Jeffrey Grantham; Shawn S. Funk; Jonathan G. Schoenecker (Case Reports in Orthopedics)
Case. An immune competent pediatric patient presented with a persistent lower extremity infection with Leclercia adecarboxylata after a penetrating injury. This case report details the presentation, clinical course, and treatment. Conclusion. Leclercia adecarboxylata has increasing reports in immunosuppressed and adult patients with musculoskeletal infection. This case now indicates that Leclercia adecarboxylata is a potential pathogen in immune competent children in musculoskeletal tissue.